Heroine Masculinity in Peaky Blinders Netflix Series Season 1 Until Season 3 - Elmosta Azzam; Hasbi Assidqi; Dadan Rusmana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research explore the representation of feminine masculinity in Peaky Blinders seasons 1-3 that portrays Polly Gray by exploring the characteristics she portrays and how her behavior conflicts or supports patriarchal power dynamics within the Shelby family and society. The study takes a qualitative descriptive approach and interprets selected critical dialogues, interactions and visual scenes. The theory of female masculinity by Halberstam (1998) is the primary theory to explain the social performance of masculinity by women, whereas the theory of hegemonic masculinity by Connell (2005) is the auxiliary theory of interpreting the negotiation of power in the structures dominated by men. The results indicate that Polly is assertive, decisive, strategic, and commands the team, and at the same time, she continues to be a woman. Her conflicts with Tommy, family and business management and her decisive steps, including getting rid of Campbell, demonstrate that feminine masculinity can be a socially intelligible and transformative power. The paper points out that the patriarchal hierarchies can be negotiated and women agency can be both performative and legitimate in cultural texts. Such findings have a role to play in the academic field of gender and media as they can help in the discussion of how female characters are able to exercise power in male-dominated situations as well as provide a more in depth examination of how gender is performed and represented in television fiction.